The Potential of Alpha-Lipoic Acid Supplementation for Non-Alcoholic Fatty Liver Disease: A Systematic Review - Prasetya, Alver; Tobian, Nikolaus; Tanjaya, Hendri; Tenggara, Riki; Loe, Luse (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2025)
Background: Insulin resistance, genetic susceptibility, oxidative stress, and inflammation lead to the development of non-alcoholic fatty liver disease (NAFLD). Alpha lipoic acid (ALA) has demonstrated benefits in enhancing insulin sensitivity and reducing inflammatory reactions in both human and animal studies. This study aims to determine the effectiveness of ALA against NAFLD.Methods: Detailed searches were conducted across several databases, including PubMed, CENTRAL, Europe PMC (medRxiv and bioRxiv), EBSCOhost (Medline), and ProQuest, using keywords such as lipoic acid, metabolic-associated fatty liver disease, steatohepatitis, and non-alcoholic fatty liver disease. Risk of bias was assessed using the Cochrane risk-of-bias tool for randomized trials.Result: Four studies were included in which the ALA effect was compared with placebo or no intervention. A significant reduction in BMI (p0.001), lipid profiles (p0.05), glycemic markers (p0.05), liver enzymes (p0.05), oxidative stress (p0.05), and fibrosis score (p0.05) was seen in NAFLD patients with ALA supplementation.Conclusion: This study shows that ALA may help manage NAFLD. However, further research is required to establish robust evidence.